Effect of technique of surfactant administration (MIST vs. InSurE) on morbidity and mortality profile of preterm neonates treated for RDS: a randomized control trial - G. M., Jeevan; Asif, Mohammed; Talikoti, Shivprasad; Kachhwaha, Ritika (International Journal of Contemporary Pediatrics, 2023)
Background: Neonatal respiratory distress syndrome is a disease affecting preterm neonates caused by insufficient pulmonary surfactant in alveoli. The reported case fatality rate is 57 to 89% in low- and middle-income countries. As there is very scanty data regarding the studies on MIST technique in India, we have generated data in our institution to compare the morbidity and mortality profile in preterm babies with RDS treated with MIST and InSurE technique. Objective was to evaluate effect of technique of surfactant administration (MIST vs. InSurE) on morbidity and mortality profile of preterm neonates treated for RDS. Methods: A Randomised controlled trial, was done on preterm neonates <34 weeks of gestation with RDS admitted in NICU between January 2020 to January 2021 who required surfactant administration. All the neonates who were fulfilling inclusion criteria after taking informed consent were randomized by colour coded chits and allotted into two groups namely Group A (MIST) & Group B (Conventional- InSurE technique). Results: A total of 100 newborns with RDS were included in the study. Among them 50 were treated with MIST and 50 with InSurE. In the present study, there is no statistically significant differences in morbity among both the study groups but there is a statistically significant difference in the incidence of mortality between two groups that is more among InSurE group. Conclusions: MIST technique is having similar morbidity profile in comparison to InSurE technique, but mortality rate is less in MIST than InSurE group.